ACCRETION AND DIFFERENTIATION OF CARBON IN THE EARLY EARTH - Tingle T.N. (My University, 1998)
The abundance of C in carbonaceous and ordinary chondrites decreases exponentially with increasing shock pressure as inferred from the petrologic shock classification of Scott et al. [Scott, E.R.D., Keil, K., Stoffler, D., 1992. Shock metamorphism of carbonaceous chondrites. Geochim. Cosmochim. Acta 56, 4281-4293] and Stoffler et al. [Stoffler, D., Keil, K., Scott, E.R.D., 1991. Shock metamorphism of ordinary chondrites. Geochim. Cosmochim. Acta 55, 3845-3867]. This confirms the experimental results of Tyburczy et al. [Tyburczy, J.A., Frisch, B., Ahrens, T.J., 1986. Shock-induced volatile loss from a carbonaceous chondrite: implications for planetary accretion. Earth Planet. Sci. Lett. 80, 201-207] on shock-induced devolatization of the Murchison meteorite showing that carbonaceous chondrites appear to be completely devolatilized at impact velocities greater than 2 km s-1. Both of these results suggest that C incorporation would have been most efficient in the early stages of accretion, and that the primordial C content of the Earth was between 10(24) and 10(25) g C (1-10% efficiency of incorporation). This estimate agrees well with the value of 3-7 x 10(24) g C based on the atmospheric abundance of 36Ar and the chondritic C/36Ar (Marty and Jambon, 1987). Several observations suggest that C likely was incorporated into the Earth's core during accretion. (1) Graphite and carbides are commonly present in iron meteorites, and those iron meteorites with Widmanstatten patterns reflecting the slowest cooling rates (mostly Group I and IIIb) contain the highest C abundances. The C abundance-cooling rate correlation is consistent with dissolution of C into Fe-Ni liquids that segregated to form the cores of the iron meteorite parent bodies. (2) The carbon isotopic composition of graphite in iron meteorites exhibits a uniform value of -5% [Deines, P., Wickman, F.E. 1973. The isotopic composition of 'graphitic' carbon from iron meteorites and some remarks on the troilitic sulfur of iron meteorites. Geochim. Cosmochim. Acta 37, 1295-1319; Deines, P., Wickman, F.E., 1975. A contribution to the stable carbon isotope geochemistry of iron meteorites. Geochim. Cosmochim. Acta 39, 547-557] identical to the mode in the distribution found in diamonds, carbonatites and oceanic basalts [Mattey, D.P., 1987. Carbon isotopes in the mantle. Terra Cognita 7, 31-37]. (3) The room pressure solubility of C in molten iron is 4.3 wt% C. Phase equilibria confirm that the Fe-C eutectic persists to 12 GPa, and thermochemical calculations for the Fe-C-S system by Wood [Wood, B.J., 1993. Carbon in the core. Earth Planet. Sci. Lett. 117, 593-607] predict that C is soluble in Fe liquids at core pressures. The abundance of 36Ar in chondrites decreases exponentially with increasing shock pressure as observed for C. It is well known that noble gases are positively correlated and physically associated with C in meteorites [e.g. Otting, W., Zahringer J., 1967. Total carbon content and primordial rare gases in chondrites. Geochim. Cosmochim. Acta 31, 1949-1960; Reynolds, J.H., Frick, U., Niel, J.M., Phinney, D.L., 1978. Rare-gas-rich separates from carbonaceous chondrites. Geochim. Cosmochim. Acta, 42, 1775-1797]. This suggests a mechanism by which primordial He and other noble gases may have incorporated into the Earth during accretion. The abundance of He in the primordial Earth required to sustain the modern He flux for 4 Ga (assuming a planetary 3 He/4 He; Reynolds et al. [Reynolds, J.H., Frick, U., Niel, J.M., Phinney, D.L., 1978. Rare-gas-rich separates from carbonaceous chondrites. Geochim. Cosmochim. Acta 42, 1775-1797] is calculated to be > or = 10(-8) cm3 g-1. This minimum estimate is consistent with a 1-10% efficiency of noble gas retention during accretion and the observed abundance of He in carbonaceous chondrites (10(-5) to 10(-4) cm3 g-1 excluding spallogenic contributions).